Circadian rhythmicity in murine blood: Electrical effects of malaria infection and anemia - Labeed, Fatima H.; Beale, Andrew D.; Schneider, Petra; Kitcatt, Stephen J.; Kruchek, Emily J.; Reece, Sarah E. (Frontiers in Bioengineering and Biotechnology, 2022)
Circadian rhythms are biological adaptations to the day-night cycle whereby cells adapt to changes in the external environment or internal physiology according to the time of day. Whilst many cellular clock mechanisms involve gene expression feedback mechanisms, clocks operate even where gene expression is absent. For example, red blood cells (RBCs) do not have capacity for gene expression, and instead, possess an electrophysiological oscillator where cytosolic potassium plays a key role in timekeeping. Here, we examined murine blood under normal conditions as well as in two perturbed states, malaria infection and induced anemia, to assess changes in baseline cellular electrophysiology and its implications for the electrophysiological oscillator. The ex-vivo blood samples were analyzed at four-hour intervals over two days by dielectrophoresis, and microscopic determination of parasitemia. We found that cytoplasmic conductivity (indicating the concentration of free ions in the cytoplasm and related to the membrane potential) exhibited circadian rhythmic behavior in all three cases (control, malaria and anemia). Compared to control samples, cytoplasm conductivity was decreased in the anemia group, whilst malaria-infected samples were in antiphase to control. Furthermore, we identified rhythmic behavior in membrane capacitance of malarial cells that was not replicated in the other samples. Finally, we reveal the historically famous rhythmicity of malaria parasite replication is in phase with cytoplasm conductivity. Our findings suggest the electrophysiological oscillator can impact on malaria parasite replication and/or is vulnerable to perturbation by rhythmic parasite activities.